2019
DOI: 10.3389/fgene.2019.00767
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges of Germline Genetic Enhancement

Abstract: The new reproductive technologies have opened the door to different processes of germline genetic enhancement by which the characteristics of an individual according to the interests of the agents involved could be selected during its gestation. Although the initiative is apparently oriented towards developing individuals that would excel in society, critical voices raise the concerns about that this approach would generate and need for a reflection on the ethical, social and legal implications of these techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 172 publications
(293 reference statements)
0
5
0
Order By: Relevance
“…However, studies have shown that using private banks has several difficulties, including a high economic cost. Public banking services are useful; however, the waitlist may be longer, putting people’s lives in jeopardy [ 118 ]. Another recurrent issue addressed in studies reviewed is the disclosure of the donor and recipient’s names, which are frequently published in government banks.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that using private banks has several difficulties, including a high economic cost. Public banking services are useful; however, the waitlist may be longer, putting people’s lives in jeopardy [ 118 ]. Another recurrent issue addressed in studies reviewed is the disclosure of the donor and recipient’s names, which are frequently published in government banks.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns led to the emergence of movements on the theme of patients' rights as well as the right of society to participate in medical decision-making [ 41 ]. Addressing ethical issues related to these technologies seems to be one of the basic requirements that must be considered in the comprehensive health system [ 42 ]. One of these issues is respect for the autonomy and independence of individuals (sick or healthy) who are entitled to choose/reject a special treatment [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies indicate that umbilical cord blood cells should not be used without parents' permission. This moral concern is right and reasonable; cord blood bank managers are required to give parents serious moral and legal guarantees about this concern [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite its potential to prevent congenital disease, germline therapy is highly controversial and there has been little research in its field for technical or ethical reasons. 1,[13][14][15] In germline gene therapy, stem cells such as sperm and eggs are modified by inserting updated genes into the genome. Modifications in this way can be made from generation to generation to create the next generation.…”
Section: Germline Gene Therapymentioning
confidence: 99%
“…In this therapy, any side effects are limited to these patients and are not passed on to the next generation. 13 In general, the individual genetic makeup is not affected by the corrected changes, but this therapy can be repaired and contribute to the normal function of the damaged organ. 16 Somatic cell gene therapy is considered the only therapy that can be accepted by society, this is because this therapy can affect cells, tissues, or organs that are targeted by sufferers and are not passed on to the next generation.…”
Section: Somatic Gene Therapymentioning
confidence: 99%